KAJIAN PUISI JERMAN MELALUI METODE SEMIOTIK - Tomasouw, Jolanda (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
As one type of literature, poetry, the unit called a rhyme, is the most unique genre. The uniqueness is due to all forms of expression that stick out in rhyme. In contrary to other literary works such as short stories, novels, or plays, poems written succinctly in the form of stanza and line. Due to the density of the message to be conveyed in such a confined space, then the choice of words and forms of writing that used very unique and complex elements by accentuating of poetic sense. That means, understanding a poem as a form of literary works the same as dealing with the texts of poems that are strung in a poetic language different with language in general. The uniqueness of the language used in the poem appeared on the use of symbols words that are figurative and the use of a distorted form of writing. Deviation form is for example the accentuation of cutting sentences or lines unreasonably, the use of words and sounds are repetitive, the use of words by imitating certain sounds or the use of meaningful associative words excessively. Modern German poetry lies in the harmony of the poetic elements that build a rhyme. Thus the resulting of rhyme and diction values and its imagery is based on how the elements that form the building of rhyme which is coherent and intact. The process of reading poetry in the context of semiotic dialectic is a process of giving meaning to a text of modern poetry through a text search in order to find the code or semiotic signs.Keywords: Puisi Jerman, Modern, Semiotika